Cellular mechanisms linking to outdoor and indoor air pollution damage during pregnancy - Chiarello, Delia I.; Ustáriz, Javier; Marín, Reinaldo; Carrasco-Wong, Ivo; Farías, Marcelo; Giordano, Ady; Gallardo, Felipe S.; Illanes, Sebastián E.; Gutiérrez, Jaime (Frontiers in Endocrinology, 2023)
Pregnancies are a critical window period for environmental influences over the mother and the offspring. There is a growing body of evidence associating indoor and outdoor air pollution exposure to adverse pregnancy outcomes such as preterm birth and hypertensive disorders of pregnancy. Particulate matter (PM) could trigger oxi-inflammation and could also reach the placenta leading to placental damage with fetal consequences. The combination of strategies such as risk assessment, advise about risks of environmental exposures to pregnant women, together with nutritional strategies and digital solutions to monitor air quality can be effective in mitigating the effects of air pollution during pregnancy.